The functional connectivity of the basal ganglia subregions changed in mid-aged and young males with chronic prostatitis/chronic pelvic pain syndrome - Lan, Xi; Niu, Xuan; Bai, Wei-Xian; Li, Hai-Ning; Zhu, Xin-Yi; Ma, Wen-Jun; Li, Jian-Long; Dun, Wang-Huan; Zhang, Ming; He, Juan (Frontiers in Human Neuroscience, 2022)
Background: The Basal ganglia (BG) played a crucial role in the brain-level mechanisms of chronic pain disorders. However, the functional changes of BG in chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) are still poorly understood. This study investigated the BG subregions' resting-state functional connectivity (rs-FC) in CP/CPPS patients compared with healthy controls. Methods: 28 patients with CP/CPPS and 28 age- and education-matched healthy males underwent clinical measurements and 3T brain MR imaging, including T1-weighted structural images and resting-state functional imaging. The data were analyzed by the seeded-based rs-FC analysis. Then, a machine learning method was applied to assess the feasibility of detecting CP/CPPS patients through the changed rs-FC. Results: Compared with healthy males, patients presented decreased rs-FC between the BG subregions and right middle cingulate cortex, and correlated with pain (r=0.51, p-uncorrected =0.005) and urinary symptoms (r=-0.4, p-uncorrected =0.034). The left superior temporal gyrus and right supramarginal gyrus showed decreased rs-FC with the BG subregions as well. The area under the receiver operating characteristic curve of 0.943 (accuracy=80%, F1-score = 80.6%) was achieved for the classification of CP/CPPS patients and healthy males with support vector machine based on the changed rs-FC. Conclusion: These findings provide evidence of altered BG subregions' rs-FC in CP/CPPS, which may contribute to our understanding of the BG's role in CP/CPPS.